Peran Tazkiyatun Nafs terhadap Regulasi Emosi Wanita Long-Distance Marriage - Tri Surani (Pusat Riset dan Inovasi Nasional, 2026)
Long-Distance Marriage (LDM) refers to a marital arrangement in which spouses experience extended physical separation due to occupational, educational, or other social obligations. Such circumstances frequently generate psychological pressures, especially for women who often carry primary responsibilities in managing household duties and caring for children independently. These challenges may trigger feelings of loneliness, stress, emotional instability, and decreased well-being. One spiritual approach considered effective in supporting emotional balance is the practice of tazkiyatun nafs, a process of inner purification and spiritual refinement. This study aims to explore the role of tazkiyatun nafs in strengthening emotion regulation among women engaged in LDM relationships. Employing a qualitative phenomenological design, data were obtained through in-depth interviews and analyzed using thematic analysis techniques. The findings demonstrate that the stages of takhalli, tahalli, and tajalli significantly enhance self-awareness, reduce negative emotional reactions, and cultivate lasting inner peace, thereby reinforcing psychological resilience in long-distance marital contexts.